Occurrence of Salmonella in ruminants and camel meat in Maiduguri, Nigeria and their antibiotic resistant pattern - Musa, Zakaria; Onyilokwu, Samson Amali; Jauro, Solomon; Yakubu, Comfort; Musa, Jasini Athanda (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study was conducted to determine the occurrence of Salmonella in various meat products (beef from cattle, chevon from goats, mutton from sheep and jaziir from camel), by screening the various selling points which includes; meat retailers in abattoir, markets and shops in Maiduguri and its environs. Materials and methods: A total of 120 samples of fresh meat from cattle, sheep, goats and camels sampled from ten meat retailers in abattoir, markets and shops in the Maiduguri metropolis, using simple random sampling technique. All samples were processed and examined according to standard bacteriological protocols. Results: Percentage occurrence of Salmonella species had the highest value of 15 (50.1%) from the market, found in sheep, while the lowest occurrence of Salmonella species was associated with 3(10.0%) in goats sampled from shop meat.. Antibiotic susceptibility pattern of Salmonella species from cattle meat revealed high resistant to Erythromycin (52%). In sheep, the higher percentage of resistance occurred against Ampicillin (33.3%) and less resistant to Amoxicillin (4%) was obtained. The isolates from camel meat recorded 25% resistant against Ampicillin, Gentamycin and 12.5% to Streptomycin. A total of 28.4% of the isolates were resistant to Ampicillin, Gentamycin and 23.1% to Ofloxacin. Conclusion: The study has shown that Salmonella species are present in fresh meat sold in abattoir, retail markets and shops. We recommend strict hygienic measures in places where fresh meat are sold in Maiduguri metropolis, Nigeria to ensure consumers right to have safe food. http://doi.org/10.5455/javar.2017.d215